Does government purchase commitment promote regular production to emergency co-production? Differential game analysis on manufacturers' production strategy - Li, Tianjiao; Jin, Yu; Fu, Xiaonan (Frontiers in Public Health, 2025)
BackgroundAs destructive diseases, governments increasingly utilize emergency co-production to satisfy the keen need for medical products. Although governments have provided purchase commitment payments to promote co-production with manufacturers, research has mainly focused on regular medical production without purchase commitment payment, whereas research on emergency co-production with purchase commitments remains scarce.MethodOur study fills the gap by analyzing the regular and emergency co-production models using differential game approaches to optimize purchase commitment.ResultsFirst, we find that even if the production and storage costs are relatively high, the emergency co-production mode sometimes has a higher production rate than the regular medical production mode. Next, the purchase commitment payment could increase the relative advantage of emergency co-production in the per-unit product value. Moreover, the emergency co-production model dominates when the demand exceeds a threshold. Furthermore, the regular medical production mode dominates the higher value and less-demanding emergency production.ConclusionsHence, both regular medical production and co-production modes can show superior performance depending on the level of demand and the degree of purchase commitment payment. Critical management insights offer takeaways for manufacturers and policy makers' decisions on emergency medical co-production to prepare for future onslaughts of destructive diseases.